'I still want to know they're not terrible people': Negotiating 'queer community' on dating apps. (May 2021) - Pym, Tinonee; Byron, Paul; Albury, Kath
Digital media has played a historical role in orienting LGBTQ+ young people's notions of 'community' around performances of identity and selfhood. In our research with LGBTQ+ dating app users aged 18–35, 'queer community' materialised in relation to participants' expectations of ethical alignment with others, with an emphasis on performing a reflexive self who was clear and consistent in what they sought on apps. Participants described apps as providing access to community, or enhancing existing connections forged via other social media or in-person contexts. In ways that both cohered with and diverged from historical framings of 'queer community', the concept emerged as a shared understanding of ethical conduct, where emotional safety and connecting with 'nice people' were prioritised. App users acknowledged the challenges of navigating the constraints and possibilities of dating app cultures and infrastructures, alongside negotiating one's political responsibilities to 'queer community'.